The mainstream of civilization - Strayer, Joseph R. (Joseph Reese) 1904-1987; Gatzke, Hans Wilhelm 1915- (Harcourt Brace Jovanovich, 1984)
Traces the history of the world's major civilizations discussing their special characteristics and contributions.